Implementation of Public Service Quality Improvement Policies in the Framework of the Bureaucratic Reform Program within the Indonesian National Armed Forces (TNI) - Pribadi Jatmiko; Eko Prasojo (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Indonesian Armed Forces or TNI is military organization that has main task and function to conduct national deffence to grant sense of security to people. Beside that, as goverment institution TNI to be charged to implement government policy of enhancement of public service quality. Enhancement of public service quality is part of bureaucracy reform or administration reform agenda through Eight Area Reform Program. The aim of the study is to analyze how TNI interpret this policy by using the variable implementation of contens and contex policy theory. The methode of this reasearch is qulitative with a post-positivst approuch. Collecting data was conducted by in- depth interview, study document and literature review. The site of research is in Indonesian Army or TNI AD which is the biggest part of Indonesian Armed Forces. Analyzing data was done by reduction, presentation, conclution and verification. The research showed that the enhancement of public service quality in contex of TNI is not significanly developed. The actors of implementation in TNI facing obstacle to understand and to interpret language, naration and terminology of this policy which is formulated tend to civil organization. They experienced dificulty to find out the equivalent terminology in TNI operational unit.